PENGARUH PRODUCT PLACEMENT REBORN RICH DAN KEMASAN TERHADAP BRAND IMAGE SCARLETT WHITENING - Angelica Ordelia; Pratiwi Cristin Harnita; Rendy Hermanto Abraham (JISOS: JURNAL ILMU SOSIAL, 2023)
Watching a film by streaming has become a new digital habit for the Indonesian people. Just like films from Indonesia, films from South Korea are also never separated from the presence of advertisements. One kind of advertising strategy that is currently used by marketers is called product placement. The purpose of this study is to determine the effect of product placement and packaging on Scarlett Whitening’s brand image in the Korean Drama Reborn Rich. This research method is a quantitative approach explanatory study, data was collected by distributing questionnaires to 128 respondents. The results of this research show that the effect of product placement and packaging on Scarlett Whitening’s brand image in the Korean Drama Reborn Rich is 17,4% on each variable